Ecdysone receptor strongly influences larval–pupal–adult transition and melanization in Tuta absoluta - Xiaodi Wang; Jiajia Wu; Jianyang Guo; Nianwan Yang; Fanghao Wan; Zhichuang Lü; Wanxue Liu (CABI Agriculture and Bioscience)
Abstract Background Tomato leaf miner (Tuta absoluta) is a quarantined pest that damages Solanaceae crops worldwide. The overuse of traditional pesticides negatively affects both human health and the environment. RNA interference (RNAi), based on double-stranded RNA (dsRNA) induction, can be beneficial in the control of Tuta absoluta; one of the key points of using this technique is the selection of target genes. Exploring the ecdysone receptors (EcR) associated with the growth and development of tomato leaf miners is an important research topic and the primary aim of this study. Methods In this study, RNA extraction, cDNA synthesis, gene cloning, bioinformatics analysis, and quantitative real-time polymerase chain reaction were used to obtain the full length, conserved domain, and relative expression levels of the EcR. RNAi was used to explore the effects of EcR on larval growth and development, pupal weight, and emergence rate. Results The full-length cDNA of T. absoluta TaEcR was 1859 bp, and the coding region including the ZnF_C4 and HOLI domains was relatively conserved. The relative expression of EcR in the early pupal stage was substantially higher than that in the other instars. Approximately 70% of TaEcR RNAi larvae died or pupated abnormally. In the few successful pupations, the pupa weights were substantially lower (36.44%) than those of the control group. The color of the pupae was abnormal, and they did not enter their normal black state; the emergence rate of pupae was reduced by 43.45% compared to that of the control group. Conclusion These results indicate that TaEcR inhibition can affect larval metamorphosis, pupation, melanism, eclosion abnormalities, and, ultimately, lead to death. The results of this study suggest that TaEcR may be a candidate factor for developing environmentally-friendly RNAi pesticides that have practical value in field control.